Urgent states in sports medicine - Mikhalyuk, E. L.; Cherepok, A. A.; Malakhova, S. N.; Михалюк, Євген Леонідович; Черепок, Олександр Олексійович; Малахова, Світлана Миколаївна (Zaporizhzhya state medical university, 2014)
Study book is intended for independent work of students of medical faculties IV course in preparation for the practical training in the discipline "Physical rehabilitation and sports medicine."